Gastrointestinal dysfunction in the intensive care unit. Issue 10 (October 2021) - Eaton, Patrick; Faulds, Matthew
Abstract: Critical illness can disrupt the many functions of the gastrointestinal (GI) system and signs of gut failure are a clear marker of critical illness severity. Prevention and management of GI dysfunction aims to improve outcomes for the critically ill patient. Early enteral nutrition is protective on the gut and encourages GI motility. A careful balance must be struck to deliver sufficient calories and protein while avoiding overfeeding with its associated complications. Gut dysmotility at any level of the GI tract is a common barrier to nutrient delivery in the critically ill. The microbiome is central to gut health and critical illness has an invariably harmful effect on its composition and function. Gut-derived sepsis is one possible consequence that carries high mortality. GI bleeding, intra-abdominal hypertension and bowel ischaemia represent severe manifestations of gut dysfunction. Management of all these complications in the ICU should involve prevention strategies, detection through regular and thorough assessment, and systematic approach to treatment.